Efficiency of unicast and broadcast gossipalgorithms for wireless sensor networks - Zanaj, Elma (Array, 2008)
Abstract: Gossip is a well-known technique for distributed computing in an arbitrarily connected network, that can be adopted effectively in wireless sensor networks. Gossip algorithms have been widely studied in previous literature, but mostly from a theoretical point of view. The aim of this paper is to verify the behavior of the gossip approach in practical scenarios, through the analysis and interpretation of simulated results. So, we investigate the impact of optimizing the neighbor selection probabilities, the effect of multiple link failures and that of limited transmission radius. The possibility to use broadcast-like algorithms to increase the rate of convergence in averaging problems is also discussed and its advantage estimated